2015
DOI: 10.1186/s12885-015-1724-9
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycans undergo differential expression alterations in right sided colorectal cancer, depending on their metastatic character

Abstract: BackgroundHeparan sulfate proteoglycans (HSPGs) are complex molecules involved in the growth, invasion and metastatic properties of cancerous cells. This study analyses the alterations in the expression patterns of these molecules in right sided colorectal cancer (CRC), both metastatic and non-metastatic.MethodsTwenty right sided CRCs were studied. A transcriptomic approach was used, employing qPCR to analyze both the expression of the enzymes involved in heparan sulfate (HS) chains biosynthesis, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 85 publications
13
60
4
Order By: Relevance
“…Except for PDAC, the overexpression of GPC1 has been observed in the tumor tissues of gliomas, ameloblastomas, prostate cancer and esophageal squamous cell carcinoma (ESCC) . However, contradictory results were observed in colorectal cancer and breast cancer . In ESCC, high levels of GPC1 were also significantly associated with chemoresistance to cisplatin .…”
Section: Discussionmentioning
confidence: 99%
“…Except for PDAC, the overexpression of GPC1 has been observed in the tumor tissues of gliomas, ameloblastomas, prostate cancer and esophageal squamous cell carcinoma (ESCC) . However, contradictory results were observed in colorectal cancer and breast cancer . In ESCC, high levels of GPC1 were also significantly associated with chemoresistance to cisplatin .…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic conditions allow for the modification of not only the expression levels or alternative gene splicing of proteoglycans but also their post‐translational modification (Datta, Pierce, & Datta, ; Iozzo & Cohen, ; Iozzo & Schaefer, ; Skandalis, Kletsas, Kyriakopoulou, Stavropoulos, & Theocharis, ). Particularly, the sulfation patterns of GAG chains in HS proteoglycans are dramatically altered (Fernández‐Vega et al, ; Lelongt et al, ; Muthana, Campbell, & Gildersleeve, ). The 6O‐sulfation, which is known to be critical for ligand interactions and activation of receptor tyrosine kinase (RTK) pathways, can be removed by extracellular sulfatases such as SULF1 and SULF2 (Lamanna, Frese, Balleininger, & Dierks, ; Wade et al, ).…”
Section: Modulation Of Brain Extracellular Matrix By Proteases and Glmentioning
confidence: 99%
“…It has been reported that 70/88 breast cancer patients presented Usp38 expression at levels lower than that of the normal expression [Armakolas et al ]. Chst14, which transfers sulfate to the C‐4 hydroxyl of N‐acetylgalactosamine residues in dermatan sulfate, showed threefold deregulation in 80% of cases for both metastatic and nonmetastatic tumors [Fernández‐Vega et al ]. EZH2‐induced silencing of Vash1 by promoter methylation has been implicated in the progression and metastasis of several cancers [Lu et al ].…”
Section: Discussionmentioning
confidence: 99%